Lymph Node Sampling and Taking of Blind Biopsies Are Important Elements of the Surgical Staging of Early Ovarian Cancer. Issue 7 (1st October 2010) - Timmers, Petra Jeanette; Zwinderman, Koos; Coens, Corneel; Vergote, Ignace; Trimbos, J. Baptist
Abstract : Background: The purpose of this study was to determine the effect of lymph node sampling and taking of blind biopsies as part of the surgical staging procedure for early ovarian cancer on disease-free survival (DFS) and overall survival (OS) in patients who received no adjuvant chemotherapy. Methods: In the EORTC ACTION Trial, 448 patients with early ovarian carcinoma were randomized between November 1990 and March 2000-224 patients to observation and 224 to adjuvant platin-based chemotherapy. Only patients allocated to observation were included for the current study. Analyses were performed in a subgroup of 75 optimally staged patients (group A), 46 patients in whom all staging steps were performed except para-aortic or pelvic lymph node sampling (group B), and 14 patients who fulfilled all staging criteria but in whom no blind peritoneal biopsies were taken (group C). The study group did not differ in stage distribution, cell type, or tumor grade. Results: Significantly improved 5-year DFS ( P = 0.03) and 5-year OS ( P = 0.01) were found in group A (optimally staged) versus group B (no lymph node sampling). A significant difference was also shown in 5-year DFS ( P = 0.02) and 5-year OS ( P = 0.003) between group A and group C (no blind biopsies). Recurrences occurred in 11 (14.6%) of 75 patients in group A, 16 (34.8%) of 46 patients in group B, and 5 (35.7%) of 14 in group C. The 5-year DFS in group A was 79% versus 61% and 64% in groups B and C, respectively. The 5-year OS decreased from 89% in group A to 71% in group B and 65% in group C. Conclusions: In this study, statistically significant differences were found in patients in whom para-aortic and pelvic lymph node sampling and taking of blind peritoneal biopsies were undertaken compared with patients in whom these staging steps had been omitted. These findings support the relevance of lymph node sampling and the taking of blind peritoneal biopsies in the surgical staging of early ovarian cancer.